PENGEMBANGAN BAHAN AJAR E-MODUL IPAS “CERFOSIS” FLIP PDF CORPORATE EDITION DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IV SD MUHAMMADIYAH AMBARBINANGUN - Ragil Alif Ramadhan; Urip Muhayat Wiji Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve low student learning achievement, which is attributed to the lack of engaging teaching materials in both face-to-face and independent learning processes. To address this issue, the researcher developed an interactive e-module containing materials, images, videos, and quizzes, hoping to enhance the learning achievement of fourth-grade students at SD Muhammadiyah Ambarbinangun in IPAS (Science, Social Studies, and Culture) subjects. This study is a research and development (R&D) project, utilizing the five-step ADDIE development model: 1) analyze, 2) design, 3) development, 4) implementation, and 5) evaluation. Data collection techniques included interviews, observations, questionnaires, and tests. Test data were analyzed using normality, homogeneity, and paired-sample t-tests. Questionnaire data were analyzed using a Likert scale. This research produced teaching materials in the form of the CERFOSIS E-module for ifourth-grade IPAS at SD Muhammadiyah Ambarbinangun, focusing on the